Leadership competencies and development for community leaders in Malaysia - Mohamad, Madinah; Silong, Abu Daud (2010)
What are the leadership competencies for community leaders in Malaysia? It attempts to identify the detailed competencies of community leaders who serve in the Neighborhood Association in Malaysia. In-depth interviews of eight participants were utilized for data collection. The interview was conducted using an interview guide for two to three hours until no more new data emerged. The data were transcribed verbatim and analyzed to identify themes and sub-themes related to competencies of community leaders in Malaysia. The research identified 10 domains of attitudes, skills, knowledge and competencies for community leaders. These were managing effective teams and work groups, building and maintaining relationship, leading diversity and difference, developing others, communicating effectively, bringing about change, solving problems, setting vision and mission, managing social and volunteer work and developing good values and leadership practices.